2019
DOI: 10.1177/0269215519831417
|View full text |Cite
|
Sign up to set email alerts
|

A therapeutic songwriting intervention to promote reconstruction of self-concept and enhance well-being following brain or spinal cord injury: pilot randomized controlled trial

Abstract: Objective: To determine the size of the effects and feasibility (recruitment and retention rates) of a therapeutic songwriting protocol for in-patients and community-dwelling people with acquired brain injury or spinal cord injury. Design: Randomized controlled trial with songwriting intervention and care-as-usual control groups, in a mixed measures design assessed at three time points. Participants: A total of 47 participants (3 in-patients with acquired brain injury, 20 community participants with acquir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…On the other hand, it is known that the method of therapeutic songwriting provides improvements in well-being in different types of clinical populations, for instance, in a retirement community (Baker & Ballantyne, 2013), in people with brain and spinal cord injuries (Baker, Rickard, Tamplin, & Roddy, 2015; Baker et al, 2019), or in young people (Baker, Jeanneret, & Clarkson, 2018). The results presented here reinforce the studies mentioned above, as the GTSW experience has provided greater well-being and mood improvements in FCGs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, it is known that the method of therapeutic songwriting provides improvements in well-being in different types of clinical populations, for instance, in a retirement community (Baker & Ballantyne, 2013), in people with brain and spinal cord injuries (Baker, Rickard, Tamplin, & Roddy, 2015; Baker et al, 2019), or in young people (Baker, Jeanneret, & Clarkson, 2018). The results presented here reinforce the studies mentioned above, as the GTSW experience has provided greater well-being and mood improvements in FCGs.…”
Section: Discussionmentioning
confidence: 99%
“…This therapeutic intervention is practiced worldwide by music therapists (Baker, Wigram, Stott, & McFerran, 2008) and has specific theoretical approaches (Baker, 2016, 2017; Myers-Coffman, Baker, & Bradt, 2020; Tamplin, Baker, Macdonald, Roddy, & Rickard, 2016). Emerging literature suggests that collaborative songwriting applied in different clinical populations stimulates feelings of connection, belonging, and group cohesion (Baker & Stretton-Smith, 2018), promotes well-being (Baker & Ballantyne, 2013; Baker, Jeanneret, & Clarkson, 2018; Baker et al, 2019), and favors health and quality of life (Grocke, Bloch, & Castle, 2009).…”
mentioning
confidence: 99%
“…Studies using heterogeneous samples have revealed a similar pattern of results. Baker et al (2019) (RCT with acquired brain injury or spinal cord injury, n = 47) found that song writing intervention improved significantly life satisfaction (Baker et al, 2019), and their earlier study (Baker et al, 2015) (acquired brain injury including TBI or spinal cord injury, n = 10) suggested that song-writing programme could support emotional adjustment after injury. (Baker et al, 2015) Nayak et al (stroke and TBI, n = 18) reported a trend towards improvement in self-and family-reported mood following a music therapy intervention in acute rehabilitation setting (Nayak et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Another limitation of our review is that we did not include studies that investigated the effects of MT on cognitive and psychological outcomes in individuals with TBI and SCI, as they fell outside the scope of our research question. Although several studies have reported the positive effects of MT on these outcomes [ 90 , 91 , 92 ], we were unable to evaluate them in our review. However, we suggest that future systematic reviews be conducted to establish the current state of evidence regarding the impact of MT on cognitive and psychological outcomes in individuals with TBI and SCI.…”
Section: Discussionmentioning
confidence: 99%